New aspects of non-alcoholic fatty liver disease - V. V. Tsukanov; E. V. Kasparov; Yu. L. Tonkikh; A. V. Vasyutin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze modern data on pathogenesis and principles of treatment of non-alcoholic fatty liver disease (NAFLD).Key points. Now concepts on genetic determinants of NAFLD and diagnostics methods develop rapidly. Treatment of NAFLD consists in application of graduated physical activity, diet modification, weight loss, application of insulin sensitizers, cytoprotective agents and antioxidants.Conclusion. Prompt development of approaches to NAFLD requires enhanced attention of medical experts to this issue.